Study on Diversity of Dragonfly (Odonata) as A Bioindicator of Water Quality in Mount Muria Area, Central Java - Saifullah Hidayat; Fiki Husnia; Ellatur Rohmah; Siti Mukhlishoh (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2019)
Water in the Mount Muria area is needed by the surrounding community to fulfill life. An indicator is needed to determine water quality. Dragonfly (Odonata) is one of the organisms as ecosystem controllers and bioindicators. This study aims to determine the diversity of dragonflies, determine water quality and describe the role of dragonflies as a bioindicator of water quality in the Mount Muria area. This type of research is descriptive quantitative research. The data collection technique used direct observation at 3 stations, namely the Colo Flower River, the Monthel Waterfall River and the River in the Rejenu Area. The results showed that there were 10 species of dragonflies consisting of 6 suborders Anisoptera and 4 suborders Zygoptera with the highest abundance value being Euphaea variegata (51.39%), Enallagma signatum (28.47%), Trithemis festiva (6.94%), Orthetrum glaucum (5.56%), Orthetrum chrysis (2.78%), Orthetrum pruinosum (2.08%), Orthetrum testaceum (0.69%), Orthetrum sabina (0.69%), Prodasineura autumnalis (0.69% ), and Drepanosticta fontinalis (0.69%). Based on water quality analysis and according to government regulation no. 82 of 2001, the water in the muria river belongs to category 2. According to the analysis of the family biotic index, it can be seen that the FBI value of the river in the Muria area is 5.60 which means the condition of the river is fair with moderate pollution levels. ©2019 JNSMR UIN Walisongo. All rights reserved.